Facile two-step synthesis of para-dithienopyrazines [data] - Hashmi, A. Stephen K.; Hüßler, Christopher; Kahle, Justin; Dietl, Martin C.; Krämer, Petra; Rominger, Frank; Rudolph, Matthias (Universität, 2024)
N-Heteropolycyclic compounds are valuable building blocks in organic electronic devices. In this work, a convenient route for the synthesis of para-dithienopyrazines from readily available starting materials is described. A cascade of nucleophilic aromatic substitution and subsequent bidirectional hydrothiolation of alkynes was used as a key step. In total, seven new target compounds were synthesized and investigated regarding their photophysical properties. In solution, these molecules act as blue emitters, which turn to green upon addition of an acid, which demonstrates their potential use as proton sensors. Data includes: CV, IR, MS, NMR, UV VIS and XRAY Data for the compounds in the manuscript